Investigation of dynamic loading of tractors with volumetric hydraulic drive - Mandryka, Volodymyr Rostyslavovych; Krasnokutskyi, Volodymyr Mykolaiovych; Ostroverkh, O. O. (Видавничий дім "Гельветика", 2020)
The processes that occur in the transmissions of tractor units and self-propelled agricultural machines under various modes of movement and in the process of regulation are characterized by complex dependencies that are studied analytically or experimentally. Various methods are known for obtaining mathematical models. One of them is the classical direct description method. Another is the use of passive and active methods of regression analysis. It is rational to use both methods, the combination of which makes it possible to obtain the necessary mathematical model. Volumetric hydraulic drive (OGP) is increasingly used in transmissions of modern tractors and self-propelled agricultural machines. The presented article discusses the mathematical description of axial piston hydraulic machines. A study of transient processes was carried out and their assessment was carried out to determine the loads arising in the transmission of the machine with a stepwise change in the load, the gear ratio of the OGP and constant fuel supply when the unit is accelerated from a standstill. The unit acceleration mode was studied while driving on plowing and during transport operations for the following parameters and such initial conditions: rotation speed of the hydraulic motor shaft and engine shaft; torque on the motor shaft; hook load; pressure in the OGP pressure line. The dynamic characteristics of hydraulic machines, fluid leaks and its elastic properties, as well as variable values of the hydraulic drive efficiency are taken into account. The simulation results are compared with experimental studies. The objects of research were: a model of a caterpillar tractor T-150E with independent full-flow OGP of the left and right sides; mock-up of a wheeled r oot harvester with independent OGP sides of the rear driving wheels. Depending on the operating modes with unsteady motion, the following control options are possible, providing high performance at a certain level of dynamic loads, or minimum dynamic loads when the time factor is not prevalent. Optimal control is also promising when additional parameters are included in the goal function.

Процеси, що виникають у трансмісіях тракторних агрегатів та самохідних сільськогосподарських машин за різних режимів руху і в процесі регулювання, характеризуються складними залежностями, які вивчаються аналітично або експериментально. Відомі різні способи отримання математичних моделей. Одним із них є класичний метод прямого опису. Іншим – використання пасивних і активних методів регресійного аналізу. Раціональним є використання обох методів, поєднання яких дає можливість отримати необхідну математичну модель. Об’ємний гідропривід (ОГП) все більше знаходить застосування в трансмісіях сучасних тракторів і самохідних сільськогосподарських машин. У наведеній статті розглядається математичний опис аксіально-поршневих гідромашин. Проведено дослідження перехідних процесів, їх оцінка проводилися для визначення навантажень, що виникають у трансмісії машини за ступінчастої зміни навантаження, передавального числа ОГП і постійної подачі палива під час розгону агрегату з місця. Режим розгону агрегату вивчався під час руху на оранці і на транспортних роботах для таких параметрів і таких початкових умов: швидкість обертання валу гідромотора і валу двигуна; крутний момент на валу двигуна; Крюкова навантаження; тиск у напірній магістралі ОГП. Враховано динамічні характеристики гідромашин, витоку рідини і її пружні властивості, а також змінні значення ККД гідроприводу. Результати моделювання зіставлені з експериментальними дослідженнями. Як об’єкти дослідження використовувалися: макет гусеничного трактора Т-150Е з незалежними повнопотоковий ОГП лівого і правого бортів; макет колісного коренезбирального комбайна з незалежними ОГП бортів задніх ведучих коліс. Залежно від режимів роботи за несталого руху можливі такі варіанти управління, що забезпечують високу швидкодію за деякого рівня динамічних навантажень або мінімальні динамічні навантаження, коли часовий чинник не є превалюючим. Перспективним є й оптимальне управління, коли у функцію мети включені додаткові параметри.
Дослідження динамічного навантаження тракторів з об'ємним гідравлічним приводом
Keywords: volumetric hydraulic drive; mathematic model; root-harvesters; transmissions of tractors; тракторні агрегати; сільськогосподарські машини; коренезбиральні комбайни; гусеничні трактори; аксіально-поршневі гідромашини